Dendritic cell-based vaccine prepared with recombinant Lactococcus lactis enhances antigen cross-presentation and antitumor efficacy through ROS production - Zhang, Tingting; Wei, Xianxian; Li, Yijie; Huang, Shuai; Wu, Yulin; Cai, Shanshan; Aipire, Adila; Li, Jinyao (Frontiers in Immunology, 2023)
Introduction Lactococcus lactis (L.L) is safe and can be used as vehicle. In this study, the immunoregulatory effect of L.L on dendritic cell (DC) activation and mechanism were investigated. The immune responses and antigen cross-presentation mechanism of DC-based vaccine prepared with OVA recombinant L.L were explored. Methods Confocal microscopy and flow cytometry were used to analyze the mechanism of L.L promoting DC maturation, phagosome membrane rupture and antigen presentation. The antitumor effect of DC vaccine prepared with L.L-OVA was assessed in the B16-OVA tumor mouse model. Results L.L significantly promoted DC maturation, which was partially dependent on TLR2 and downstream MAPK and NF-κB signaling pathways. L.L was internalized into DCs by endocytosis and did not co-localized with lysosome. OVA recombinant L.L enhanced antigen cross-presentation of DCs through the phagosome-to-cytosol pathway in a reactive oxygen species (ROS)- and proteasome-dependent manner. In mouse experiments, L.L increased the migration of DCs to draining lymph node and DC vaccine prepared with OVA recombinant L.L induced strong antigen-specific Th1 and cytotoxic T lymphocyte responses, which significantly inhibited B16-OVA tumor growth. Conclusion This study demonstrated that recombinant L.L as an antigen delivery system prepared DC vaccine can enhance the antigen cross-presentation and antitumor efficacy.